Creation of effective subsystems and organizational structures as regulatory mechanisms for management of innovation implementation processes in construction companies - Chupryna, Kh.; Ivinsky, E.; Dmytriuk, D.; Mykytchenko, B.; Logachov , T. (Ways to Improve Construction Efficiency, 2023)
In today’s dynamic business environment, especially in the construction industry, the implementation of innovations is becoming a key factor in ensuring the competitiveness of companies. The effectiveness of innovation implementation processes depends not only on the quality of the innovations themselves, but also on how the management subsystems in the company are organized and structured. The creation of adaptive subsystems and organizational structures that function as regulatory mechanisms is necessary for the successful management of innovation processes. Management subsystems can include various elements, such as communication channels, control mechanisms, risk assessment and management decisions. It is important that these elements are not only effective, but also flexible, because the construction sector is subject to numerous changes, which may be due to external and internal factors, such as changes in legislation, market trends and technological innovations. Organizational structures that support innovation processes should ensure a clear distribution of responsibilities and authorities, promote cooperation between departments and reduce bureaucracy that can slow down the processes of implementing innovations. Such structures allow you to focus on achieving the strategic goals of the company, and also contribute to a rapid response to changes in the environment. Research in this area involves the analysis of factors that influence the creation of effective subsystems and organizational structures, as well as their role in increasing the efficiency of innovation processes. The use of modern methods and approaches to management allows construction companies not only to adapt to new conditions, but also to actively shape their own environment for implementing innovations. The creation of effective subsystems and organizational structures in construction companies is an important step in optimizing innovation implementation processes, which contributes to increasing the overall economic productivity of enterprises and ensuring their sustainability in a competitive environment.